Preparation method and application of carbon aerogel coated cobalt sulfide / phosphide nanoparticle composite

CN116676628BActive Publication Date: 2026-10-27NORTHWEST NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310725585.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2026-10-27
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

然而,单一催化剂局限性较大,仍然远远不能满足工业化的需求

Benefits of technology

[0022]本发明与现有技术相比具有以下优点:碳气凝胶包覆纳米粒子复合材料

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116676628B_ABST
    Figure CN116676628B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a carbon aerogel coated cobalt sulphide / phosphide nanoparticle composite material, which comprises the following steps: dissolving chitosan powder in an ice acetic acid aqueous solution to form a hydrogel with a certain viscosity; then adding cobalt salt, melamine phosphate and thiourea into the chitosan hydrogel and performing freeze drying; and naturally cooling the dried sample after heat treatment in a N2 atmosphere to obtain the final composite material. The biomass chitosan is used as a main carbon source, the melamine phosphate is used as a phosphorus source, and the thiourea is used as a sulfur source, so that the synthesis steps are simple, environment-friendly and low in cost. The composite material has excellent catalytic activity and good stability for electrocatalytic hydrogen evolution, oxygen evolution and water full decomposition reaction. Especially, the catalytic OER activity of the composite material is much higher than that of a noble metal catalyst RuO2, and the composite material has a good application prospect in the hydrogen production technology by electrolysis of water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the preparation and application of a carbon aerogel-coated cobalt-sulfur / phosphide nanoparticle composite material, and more particularly to a cobalt-sulfur / phosphide nanoparticle composite material prepared using melamine phosphate as a phosphorus source and thiourea as a sulfur source, which is mainly used for electrocatalytic hydrogen evolution (HER), oxygen evolution (OER) and water electrolysis reactions in alkaline media. Background Technology

[0002] Hydrogen production through water electrolysis can be powered by solar, tidal, and wind energy, meeting the needs of clean and sustainable energy development. However, during water electrolysis, the high overpotentials and slow kinetic rates of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) result in high decomposition voltage and low efficiency, hindering the large-scale application of this technology. Therefore, developing highly efficient HER and OER electrocatalysts is crucial for improving water electrolysis efficiency and promoting its large-scale application. To date, Pt-based (Pt / C) and Ru / Ir-based catalysts (RuO2 and IrO2) are considered the most effective HER and OER electrocatalysts, respectively. However, these noble metal catalysts are scarce, costly, and unstable, limiting their large-scale commercial application. Therefore, developing highly active water electrolysis catalysts that are abundant, easy to prepare, and stable is an inevitable choice for developing hydrogen production technology through water electrolysis.

[0003] In recent years, various types of non-precious metal-based catalysts have been reported. Among them, transition metal-based oxides, phosphides, sulfides, nitrides, and hydroxides have been extensively studied to explore catalysts with high activity and low cost. First transition metals, especially cobalt-based catalysts, exhibit high OER activity and are characterized by abundance, low price, and good stability. However, single catalysts have significant limitations and still fall far short of industrial needs. Therefore, only by constructing multi-component composite catalysts can the complementary and synergistic advantages of different components be achieved, thereby improving the intrinsic activity and multifunctionality of the catalyst. Recently, the construction of composite catalysts with heterogeneous interfaces by combining multiple active components has attracted widespread attention in the electrocatalytic water splitting. In addition, combining catalysts with carbon materials (such as graphene, carbon nanotubes, graphitized carbon materials, etc.) is an effective strategy to improve the electrocatalytic activity of catalysts. Carbon materials can not only improve the conductivity of the catalyst but also protect the active components from rapid oxidation and deactivation during the catalytic OER process.

[0004] Based on the above considerations, this invention provides a simple, efficient, and controllable method for preparing carbon aerogel-coated Co9S8 / Co2P nanoparticle composite materials. The prepared composite catalyst exhibits excellent catalytic activity and good stability for electrocatalytic hydrogen evolution, oxygen evolution, and the complete decomposition of water. In particular, its catalytic activity for OER is much higher than that of the noble metal catalyst RuO2, showing great promise for application in water electrolysis hydrogen production technology. Summary of the Invention

[0005] The purpose of this invention is to provide a simple, effective, and controllable method for preparing a carbon aerogel-coated Co9S8 / Co2P nanoparticle bifunctional composite catalyst, and to test the performance of the prepared composite catalyst in catalyzing HER, OER, and water electrolysis.

[0006] I. Preparation of carbon aerogel-coated Co9S8 / Co2P nanoparticle composite materials The preparation of the carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material of the present invention includes the following process steps: (1) Preparation of hydrogel precursor: Chitosan powder was added to distilled water, and then glacial acetic acid was added and stirred thoroughly to form a hydrogel. The volume ratio of glacial acetic acid to distilled water was 1:100~1:150; the concentration of chitosan powder in glacial acetic acid and distilled water was 10~25 mg / mL.

[0007] (2) A certain amount of CoCl·6H2O, melamine phosphate (MP), and thiourea were added to the chitosan hydrogel and freeze-dried. The dried sample was then heat-treated at 800°C for 1-3 h (preferably 2 h) under N2 atmosphere at a heating rate of 4-6 °C / min (preferably 5 °C / min), followed by natural cooling. The cobalt salt was one of Co(CH3COO)2·4H2O, CoCl2·6H2O, or Co(NO3)2·6H2O. The molar ratio of melamine phosphate to thiourea was 1:1-1:4, and the ratio of the amount of cobalt salt to the total amount of melamine phosphate and thiourea was 2:1-1:3.

[0008] The prepared carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material consists of three components: Co9S8, Co2P, and carbon aerogel. The content of Co9S8 is 35.2%-47.3%, the content of Co2P is 12.5%-24.1%, and the content of carbon is 28.6%-52.3%. The particle size of Co9S8 and Co2P nanoparticles is 10-50 nm. The specific surface area of ​​the composite material is 105-201 m². 2 / g, pore volume is 0.10-0.15cm³ 3 / g.

[0009] II. Structure of Carbon Aerogel-Coated Co9S8 / Co2P Nanoparticle Composite Material Figure 1 This is a SEM image of the catalyst prepared in Example 1 of this invention. As can be seen from the image, the prepared catalyst maintains the three-dimensional porous structure of carbon aerogel.

[0010] Figure 2 This is a TEM image of the catalyst prepared in Example 1 of this invention. As can be seen from the image, Co9S8 / Co2P nanoparticles are embedded in carbon aerogel, with a particle size of 10-50 nm.

[0011] Figure 3 The following are XRD patterns of the catalysts prepared in Examples 1-3 of this invention: (a) Example 1; (b) Example 2; (c) Example 3. As shown in the figures, all prepared catalysts consist of three components: Co9S8, Co2P, and C. The diffraction peaks at 2θ of 15.4, 25.3, 29.8, 31.2, 39.6, 44.7, 47.6, and 52.1° correspond to the diffraction peaks of the (111), (220), (311), (222), (331), (422), (511), and (440) crystal planes of Co9S8, respectively. The characteristic peaks at 2θ of 40.9, 44.1, 55.4, and 70.5° correspond to the diffraction peaks of the (201), (130), (040), and (132) crystal planes of Co2P, respectively.

[0012] Figure 4 The following are Raman spectra of the catalysts prepared in Examples 1-3 of this invention: (a) Example 1; (b) Example 2; (c) Example 3. The three catalysts were analyzed at 1356 cm⁻¹. -1 and 1600cm -1 The presence of D and G bands of carbon materials at these locations indicates the presence of carbon materials in the catalyst. The I bands of the three catalysts... D / I G The values ​​are all less than 1, indicating that the carbon material in the prepared catalyst has a high degree of graphitization and good electrical conductivity.

[0013] Figure 5 This is the N2 adsorption-desorption isotherm of the catalyst prepared in Example 1 of this invention. The isotherm shows that the obtained sample exhibits a typical type IV isotherm and has an H3 type hysteresis loop, indicating that the sample has a multi-level porous structure.

[0014] Figure 6 This is a pore size distribution diagram of the catalyst prepared in Example 1 of the present invention. As can be seen from the figure, the obtained sample has a wide pore size distribution range, mainly concentrated around 2-6 nm, which further proves that the catalyst has a rich mesoporous structure.

[0015] III. Properties of Carbon Aerogel-Coated Co9S8 / Co2P Nanoparticle Composites The composite material was used to fabricate working electrodes for electrocatalytic hydrogen evolution, oxygen evolution, and water electrolysis. A certain amount of the composite material was ultrasonically dispersed in ethanol, and an appropriate amount of 5% Nafion solution was added and mixed evenly to prepare a suspension. A certain amount of this suspension was drop-coated onto a glassy carbon electrode and allowed to air dry to prepare working electrodes for electrocatalytic hydrogen evolution and oxygen evolution; a certain amount of this suspension was also drop-coated onto treated nickel foam to prepare a working electrode for electrocatalytic water splitting. Electrochemical performance was tested using a CHI760E electrochemical workstation.

[0016] Figure 7 This is the LSV curve of the catalyst prepared in Example 1 of this invention catalyzing HER in 1.0 M KOH. As shown in the figure, the obtained catalyst achieves a current density of 10 mA / cm² when catalyzing HER in 1.0 M KOH. 2 The overpotential was 174 mV, demonstrating that the catalyst has excellent catalytic activity for HER.

[0017] Figure 8 This is the LSV curve of the catalyst prepared in Example 1 of this invention catalyzing OER in 1.0 M KOH. As shown in the figure, the obtained catalyst achieves a current density of 10 mA / cm² when catalyzing OER in 1.0 M KOH. 2 The overpotential was 262 mV, which proves that the catalyst has excellent catalytic activity for OER.

[0018] Figure 9 The figure shows the LSV curve of the catalyst prepared in Example 1 of this invention for catalytic water electrolysis in 1.0 M KOH. As can be seen from the figure, the obtained catalyst achieves a current density of 10 mA / cm² during the total decomposition of water in 1.0 M KOH. 2 The decomposition voltage was 1.56 V, proving that the catalyst, as a bifunctional catalyst for HER and OER, has excellent catalytic activity for water electrolysis.

[0019] Figure 10 This is the voltage-time curve of the catalyst prepared in Example 1 of this invention for catalytic water electrolysis in 1.0 M KOH. As shown in the figure, after 22 h of stability testing, the potential value of the obtained catalyst increased by only 46 mV, proving that the catalyst has good stability in the process of catalytic water electrolysis.

[0020] In summary, the test results show that in a 1.0 M KOH solution, at 10 mA / cm 2 At current densities, the overpotential of HER can be as low as 174 mV, the overpotential of OER can be as low as 262 mV, the decomposition voltage of water electrolysis can be as low as 1.56 V, and it has good cycle stability.

[0021] The reaction mechanism of this invention is as follows: Chitosan is used as the main carbon source, melamine phosphate as an auxiliary carbon and phosphorus source, and thiourea as a sulfur source. Chitosan powder is dissolved in an aqueous solution of glacial acetic acid to form a hydrogel with a certain viscosity. Cobalt source, melamine phosphate (MP), and thiourea are added to the chitosan hydrogel, and then freeze-dried. The abundant -P-OH and -P=O groups in melamine phosphate and the abundant -OH groups in chitosan have strong coordination ability, which can uniformly disperse and stably chelate metal ions through coordination. The dried sample is heated at 750~850℃ for 1~2 h under N2 atmosphere at a heating rate of 5.0 ℃ / min, followed by natural cooling. During the high-temperature carbonization process, metal ions are converted into metal sulfides and phosphides, thus obtaining a carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material. The composition, structure, and catalytic performance of a catalyst can be controlled by adjusting the ratio of melamine phosphate to thiourea, the ratio of cobalt salt to (melamine phosphate + thiourea), and the temperature and reaction time of the heat treatment. For example, increasing the proportion of thiourea can increase the Co9S8 content in the catalyst, and increasing the reaction temperature can reduce the volume of the generated carbon aerogel.

[0022] Compared with the prior art, the present invention has the following advantages: carbon aerogel-coated nanoparticle composite material. 1. By effectively combining the two active components Co9S8 and Co2P, an effective synergistic effect and heterogeneous interface can be formed between the different components, which endows the catalyst with excellent intrinsic catalytic activity of HER and OER bifunctionality and superior interfacial charge transport rate, thus accelerating the electrocatalytic reaction.

[0023] 2. Using melamine phosphate as the phosphorus source and thiourea as the sulfur source avoids the generation of toxic gases and reduces environmental pollution compared to commonly used inorganic phosphorus / sulfur sources.

[0024] 3. Using biomass chitosan as raw material, the strong coordination between the numerous coordinating groups contained in chitosan and melamine phosphate and metal ions is utilized to chelate the metal ions, thereby ensuring that the elements in the final catalyst are evenly distributed.

[0025] 4. The core-shell structure formed can not only further improve the conductivity of the composite material, but also prevent the loss of active components in the electrocatalytic process to a certain extent.

[0026] 5. Activity tests show that the composite material prepared in this invention has excellent electrocatalytic activity for hydrogen evolution, oxygen evolution and water electrolysis reactions, and has good stability in alkaline media, showing great application prospects. Attached Figure Description

[0027] Figure 1This is a SEM image of the catalyst prepared in Example 1 of this invention.

[0028] Figure 2 This is a TEM image of the catalyst prepared in Example 1 of the present invention.

[0029] Figure 3 Here are the XRD patterns of the catalysts prepared in Examples 1-3 of this invention: (a) Example 1; (b) Example 2; (c) Example 3.

[0030] Figure 4 These are the Raman spectra of the catalysts prepared in Examples 1-3 of this invention.

[0031] Figure 5 This is the N2 adsorption-desorption isotherm of the catalyst prepared in Example 1 of this invention.

[0032] Figure 6 This is a pore size distribution diagram of the catalyst prepared in Example 1 of the present invention.

[0033] Figure 7 This is the LSV curve of HER catalyzed by the catalyst prepared in Example 1 of this invention in 1.0 M KOH.

[0034] Figure 8 This is the LSV curve of the catalyst prepared in Example 1 of this invention catalyzing OER in 1.0 M KOH.

[0035] Figure 9 This is the LSV curve of the catalyst prepared in Example 1 of this invention for catalytic electrolysis of water in 1.0 M KOH.

[0036] Figure 10 This is the voltage-time curve of the catalyst prepared in Example 1 of this invention for catalytic electrolysis of water in 1.0 M KOH. Detailed Implementation

[0037] The present invention will now be described in more detail through specific embodiments.

[0038] Example 1 (1) Preparation of carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material: 1.000 g of chitosan powder was added to 50 mL of distilled water. Then, 400 μL of glacial acetic acid was added to the chitosan aqueous solution to form a hydrogel with a certain viscosity. 1.3324 g (5.6 mmol) CoCl·6H2O, 0.3586 g (1.6 mmol) melamine phosphate (MP) and 0.3045 g (4.0 mmol) thiourea were added to the chitosan hydrogel and freeze-dried at -50 ℃ for 36 h. The molar ratio of melamine phosphate to thiourea was 1:2.5, and the molar ratio of CoCl·6H2O to (melamine phosphate + thiourea) was 1:1. The dried sample was heat-treated in a N2 atmosphere at a rate of 5.0 °C / min to 800 °C for 2.0 h, followed by natural cooling to obtain the composite material, named Co9S8 / Co2P@CA (CA represents carbon aerogel). The prepared composite material possesses a three-dimensional porous structure of carbon aerogel. Figure 1 The particle size of Co9S8 and Co2P nanoparticles is 10-50 nm. Figure 2 The composite material consists of three components: carbon aerogel, Co9S8, and Co2P. Figure 3 The content of Co9S8 is 41.2%, the content of Co2P is 18.5%, and the content of carbon is 40.3%; the carbon material's I D / I G It is 0.98 ( Figure 4 The specific surface area of ​​the composite material is 189 m². 2 / g ( Figure 5 The pore volume is 0.14 cm³. 3 / g ( Figure 6 ).

[0039] (3) Catalytic performance test Test Method: Weigh 5.0 mg of the prepared catalyst and add it to a solution of 0.5 mL anhydrous ethanol and 10 μL Nafion (DuPont, 5 wt%). Sonicate for 30 min, and then take 5 μL of the suspension and coat it onto a 3 mm glassy carbon electrode. Using the prepared glassy carbon electrode as the working electrode, a graphite electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and 1.0 M KOH as the electrolyte, perform HER and OER tests in a three-electrode system. For the water electrolysis performance test, a two-electrode system is used. The prepared suspension is dropped onto two thoroughly cleaned 1 cm electrodes. 2 On the nickel foam, the catalyst loading was 1 mg / cm³. 2 The cathode and anode were fabricated and tested in a 1.0 M KOH solution. Stability testing was performed at a current density of 10 mA / cm². 2The following method is used to test the potential-time curve.

[0040] Test results: at a current density of 10 mA / cm² 2 At that time, the overpotential for HER catalysis by this catalyst was 174 mV ( Figure 7 The overpotential for catalytic OER is 262 mV. Figure 8 The decomposition voltage of catalytic water electrolysis is 1.56 V (10 mA / cm). 2 hour)( Figure 9 After a 22-hour stability test, the catalyst's potential increased by only 46 mV. Figure 10 These results demonstrate that the catalyst exhibits excellent activity and stability in catalyzing HER, OER, and water electrolysis.

[0041] Example 2 (1) Preparation of carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material: Except for the amount of thiourea (0.1827 g, 2.4 mmol) and the molar ratio of melamine phosphate to thiourea (1:1.5), the other steps were the same as in Example 1. The prepared composite material has a three-dimensional porous structure of carbon aerogel, and the particle size of Co9S8 and Co2P nanoparticles is 10-50 nm; the composite material is composed of three components: carbon aerogel, Co9S8, and Co2P, with the content of Co9S8 being 37.5%, the content of Co2P being 23.6%, and the content of carbon being 38.9%; the carbon material I D / I G The specific surface area of ​​the composite material is 172 m², which is 0.97. 2 / g, pore volume is 0.13cm³ 3 / g.

[0042] (3) Catalytic performance test Test method: Same as Example 1.

[0043] Test results: at a current density of 10 mA / cm² 2 At that time, the overpotential for catalytic HER was 245 mV, the overpotential for catalytic OER was 314 mV, and the decomposition voltage for catalytic water electrolysis was 1.58 V (10 mA / cm). 2 (Time). After a 22-hour stability test, the catalyst's potential increased by 50 mV.

[0044] Example 3 (1) Preparation of carbon aerogel-coated Co9S8 / Co2P nanoparticle composite material: Except for the amount of CoCl·6H2O being 2.6648 g (11.2 mmol) and the molar ratio of CoCl·6H2O to (melamine phosphate + thiourea) being 2:1, the other steps were the same as in Example 1. The prepared composite material has a three-dimensional porous structure of carbon aerogel, and the particle size of Co9S8 and Co2P nanoparticles is 10-50 nm; the composite material is composed of three components: carbon aerogel, Co9S8, and Co2P, with the content of Co9S8 being 43.6%, the content of Co2P being 24.1%, and the content of carbon being 32.3%; the carbon material I D / I G The specific surface area of ​​the composite material is 123 m², which is 0.95. 2 / g, pore volume 0.10cm³ 3 / g.

[0045] (3) Catalytic performance test Test method: Same as Example 1.

[0046] Test results: at a current density of 10 mA / cm² 2 At that time, the overpotential for catalytic HER was 218 mV, the overpotential for catalytic OER was 295 mV, and the decomposition voltage for catalytic water electrolysis was 1.57 V (10 mA / cm). 2 (Time). After a 22-hour stability test, the catalyst's potential increased by 45 mV.

Claims

1. A method for preparing a carbon aerogel-coated cobalt-sulfur / phosphide nanoparticle composite material, comprising the following process steps: (1) Preparation of hydrogel precursor: Chitosan powder was added to distilled water, and then glacial acetic acid was added and stirred thoroughly to form a hydrogel; (2) Preparation of carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material: cobalt salt, melamine phosphate and thiourea were added to chitosan hydrogel and freeze-dried. The dried sample was then heated to 750~850℃ for 1~2 h at a rate of 5.0 ℃ / min under N2 atmosphere and then cooled naturally to obtain carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material. in, The molar ratio of melamine phosphate to thiourea is 1:1 to 1:4; the ratio of the amount of cobalt salt to the total amount of melamine phosphate and thiourea is 2:1 to 1:

3.

2. The method for preparing the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material as described in claim 1, characterized in that: In step (1), the volume ratio of glacial acetic acid to distilled water is 1:100~1:150; the concentration of chitosan powder in glacial acetic acid and distilled water is 10~25 mg / mL.

3. The method for preparing the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material as described in claim 1, characterized in that: In step (2), the cobalt salt is one of Co(CH3COO)2·4H2O, CoCl2·6H2O, or Co(NO3)2·6H2O.

4. The method for preparing the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material as described in claim 1, characterized in that: The prepared composite material consists of three components: carbon aerogel, Co9S8, and Co2P. The content of Co9S8 is 35.2%-47.3%, the content of Co2P is 12.5%-24.1%, and the content of carbon is 28.6%-52.3%. The particle size of the Co9S8 and Co2P nanoparticles is 10-50 nm. The specific surface area of ​​the composite material is 105-201 m². 2 / g, pore volume is 0.10-0.15cm³ 3 / g.

5. The application of the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material prepared by the method described in claim 1 in the electrocatalytic hydrogen evolution reaction.

6. The application of the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material prepared by the method described in claim 1 in the electrocatalytic oxygen evolution reaction.

7. The application of the carbon aerogel-coated cobalt sulfide / phosphide nanoparticle composite material prepared by the method described in claim 1 in the electrocatalytic water splitting reaction.

Citation Information

Patent Citations

  • Nitrogen-sulfur double-doped carbon material difunctional oxygen catalyst and preparation method and application thereof

    CN106207204A

  • Preparation method of cross-linked carbon nanosheet loaded cobalt monoatom

    CN115505960A